Ecological impact on the environment of laser space solar power plants - Melnikov, Vitaly; Maignan, Schubert; Kozhanova, Evgenia (Nexo Revista Científica, 2022)
Climate stabilization and replacement of oil with alternative energy sources are urgent problems in the modern world. Space solar power plants [SSPP] can solve these problems simultaneously. Based on the review of literary sources, we raised one of the primary issues of the SSPP creation related to the need to identify the nature and the extent of its impact on the environment. First, we analyzed the environmental impact of the SSPP and traditional energy sources (thermal power plants, nuclear power plants, and hydroelectric power plants). Second, we considered the environmental impact of various wireless transmission methods of energy from the SSPP: ultrahigh-frequency (microwave) and infrared [IR] laser radiation, and the efficiency of energy transmission from the SSPP. One should emphasize the specific concept of efficiency for these power plants since they have an infinite energy source in the form of the Sun. Thus, the superiority of space solar power plants lies in the absence of nuclear radiation and chemical toxicity, a much higher efficiency, locality of impact (a site with a diameter of 40–50 m on Earth when broadcasting from a geostationary orbit), and a lower cost. For several reasons, mainly due to the terrorist threat, it is advisable to abandon the use of tethered balloons for receiving laser radiation above the clouds to eliminate losses in the atmosphere and carry out a live broadcast and reception of energy on the Earth, creating lasers operating in the windows of atmospheric transparency. One can use local illumination of the atmosphere during the operation of these power plants. The use of laser SSPP is especially relevant for solving the problems of the Arctic and continental shelf development with an extreme climate (taiga and tundra with swamps and permafrost) and for mobile objects and transport.